2002
DOI: 10.1046/j.1472-8206.2002.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Do endogenous opioids contribute to the bradycardia of rats with obstructive cholestasis?

Abstract: Endogenous opioids have nitric oxide (NO)-dependent cardiovascular actions. In the light of biological evidence of accumulation of endogenous opioids in cholestasis and also existence of NO-dependent bradycardia in cholestatic subjects, this study was carried out to evaluate the role of endogenous opioids in the generation of bradycardia in a rat model of cholestasis. Male Sprague-Dawley rats were used to induce cholestasis by surgical ligation of the bile duct, with sham-operated animals serving as a control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
41
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 36 publications
9
41
0
1
Order By: Relevance
“…Although opioid peptides were first recognized in brain, they are also found in other tissues such as gut, spleen, stomach, heart, pancreas and liver (38). Opioid peptides are up regulated in diseases states such as liver dysfunction, endotoxic shock, trauma and cholestasis (7,11,14). Morphine administration is shown to induce oxidative stress and increase superoxide dismutase and catalase activities and apoptosis in liver tissue (32).…”
mentioning
confidence: 99%
“…Although opioid peptides were first recognized in brain, they are also found in other tissues such as gut, spleen, stomach, heart, pancreas and liver (38). Opioid peptides are up regulated in diseases states such as liver dysfunction, endotoxic shock, trauma and cholestasis (7,11,14). Morphine administration is shown to induce oxidative stress and increase superoxide dismutase and catalase activities and apoptosis in liver tissue (32).…”
mentioning
confidence: 99%
“…Opioid peptides contribute partly to the manifestations of liver disease such as fatigue, pruritis, ascitis and hepatic encephalopathy. There are also emerging reports on the role of opioid system in the pathophysiology of cardiovascular hyporesponsiveness in short-term cholestasis [4,5]. However there is not any data regarding the contribution of endogenous opioid system to hyperdynamic circulation of cirrhosis which is a more common clinical situation with worldwide importance.…”
Section: Introductionmentioning
confidence: 98%
“…These destructive effects of opium have been also observed in biliary systems so that a significant increase in the range of the common bile duct diameter in comparison with normal bile ducts was shown following chronic opium addiction [3]. Besides, it has been suggested that opioid neurotransmission is increased in patients with liver disease, and therefore, administration of opioid antagonists decreases liver injury in animal models with acute biliary obstruction [4,5]. Moreover, the current data suggest that regular injection of opioids may lead to decreased hepatic glutathione levels [6].…”
Section: Introductionmentioning
confidence: 93%